Mangrove area degradation and management strategies in Indonesia: A review - Utami, Westi; Sugiyanto, Catur; Rahardjo , Noorhadi (Brawijaya University, 2024)
Coastal communities are particularly vulnerable to the effects of climate change. This study aimed to review the impact of land use change and mangrove degradation on coastal areas and analyze the problems and strategies of mangrove management in Indonesia. Journal data sources were obtained from the Scopus and Google Scholar databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was used in the study. The results indicate that economic activities such as mining, industry, and ponds are the main cause of mangrove damage, which in turn leads to increased disasters, CO2 emissions, and decreased community income. To address this issue, mangrove management strategies that take into account social, economic, and environmental factors are necessary. Successful mangrove restoration requires increased inclusion, community capacity, budgeting, and stakeholder involvement. Government policies regulating sustainable spatial planning, law enforcement, and institutional frameworks are crucial components of mangrove management. The study's results are expected to serve as the foundation for developing sustainable coastal management strategies that enhance the safety of coastal communities from disasters and improve their welfare.